On being a therapist, a tutor, a researcher and just another community member - Simon, Gail (Murmurations: Journal of Transformative Systemic Practice, 2023)
Writings from 2007 In 2007, I had “one of those years”. Many dreadful things happened. I hear myself think, “It could have been worse”. Nevertheless, it was a challenging year for me. And doing work which is all about supporting others with their struggles, their work, their learning was sometimes tough, frequently moving. I was aware of how I was drawing on the experiences of clients and trainees and other people I had met who had faced serious illness or death. Despite my commitment to limit imbalance of power in therapy, the experience of loss and illness created a sense of levelling that I had not anticipated. I chose to “come out” from behind that generic version of me as therapist, trainer, researcher and reveal more to people than I was used to. I’m not entirely sure how much I made a choice to do that but I did try to manage things in a professional manner. Whatever that means. Four particular conversational clusters stood out for me that took place during that year. I wrote them at the time but I see that I have written them in the past tense. I think I needed to. Put them in the past. I was, in some ways, still in shock so writing in the past tense helped me create a timeline to locate me in another time zone known as The Present. It was a better place to be and one from which I could create another perspective.